Quantity surveyors and their competencies in the provision of PFI services - Khairuddin, Samer Shahedza; Abdul Rashid, Khairuddin (Construction Research Institute of Malaysia, 2016)
This paper concerns Quantity Surveyors and their competencies in the provision of PFI services. It begins with the respective overviews on the quantity surveying profession and Public Private Partnership (PPP) in Malaysia. Generally, QSs are engaged to provide construction related professional services including procurement, costing and contractual advisory services. PPP was utilized as a compliment to the conventional procurement approach, in the provision of public infrastructure and services, initially in 1983 via Privatization, and subsequently in 2006 via the Private Finance Initiative or PFI. Among the key reasons why the government adopted PPP include constraints in the public purse and to meet the demand for higher level quality in public infrastructure and services. In the context of PPP projects, past studies suggested that Malaysian professionals including QSs do not adequately possess the appropriate skills and expertise to provide such services including PFI. In an attempt to better understand the competency levels of QSs in general and in relation to PFI services a study employing the method of content analysis of three past studies on the subject matter was conducted. From the content analysis a total of seven (7) main competencies and their respective forty six (46) sub-competencies were identified. Thereafter data obtained from these past studies was micro-analysed and contrasted with the QSs professional services as promoted by the Board of Quantity Surveyors Malaysia (BQSM). The key outcomes of the analysis revealed the presence of a relationship between the competencies of QS professional services and PFI services implying QSs are reasonably well positioned to acquire those PFI skills and therefore are able to provide high quality PFI services; and the presence of a 'competency gap' in each of the seven PFI (7) main competencies. The latter implies that the QS profession in actuality suffers from what can be referred to as a 'multi-dimensional deficiency'. In the light of the presence of 'multi-dimensional deficiency' in the provision of PFI services among QSs, the paper recommends that the QS profession should consider initiating a structured and holistic approach in capacity building for its members.